Food Security Status and its Determinants among Rural Households of Tach Gaint District, North West Ethiopi - Yismaw Assefa (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2022)
Food security is a challenge facing all countries, especially those in Sub-Sahara Africa. Ending hunger, achieving food security, and improving nutrition are the Nations' 2030 core goals which Ethiopia is striving to attain. Therefore, assessing rural household food security contributes to this effort. Accordingly, the present study intended to investigate the determinants of rural food security at the household level in Tach Gaint district, South Gondar Zone, Amhara region. The study employed a cross-sectional research design com- posed of both quantitative and qualitative research approaches. It used a random sampling technique to select sample households. Household surveys, key informant interviews, and focused group discussions were conducted to collect primary data. A total of 200 house- holds were covered by the questionnaire survey. Data were analyzed using descriptive and inferential statistics. The study revealed that nearly half of the sampled households were food insecure. The binary logistic regression results showed seven out of twelve explanatory variables: sex, household size, livestock number in Tropical Livestock Unit, farmland size, oxen number, age, and credit access as determinants of household food security. In conclu- sion, the determinants of food security are complex and call for multifaceted interventions. Such efforts should include resettling food insecure households where better land resources are available, establishing skill training centers for farming households, enhancing rural credit services,and expanding and improving family planning services.